2017
DOI: 10.1111/coa.12834
|View full text |Cite
|
Sign up to set email alerts
|

The increased expression of TCF3 is correlated with poor prognosis in Chinese patients with nasopharyngeal carcinoma

Abstract: Our observations suggest, for the first time, that TCF3 is significantly associated with the development and progression of NPC, which can be used as an important prognostic marker for patients with NPC and may be an effective target for the treatment of NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…TCF1 (TCF7) has also been shown to be overexpressed in renal cell carcinoma 19. Interestingly, Shen et al demonstrated that another member of LEF/TCF family, TCF3, had a higher expression in NPC than in non-tumorous nasopharyngeal tissues, and they also confirmed that increased expression of TCF3 was closely related to clinical stage, locoregional recurrence and distant metastasis of NPC, and thus resulted in shorter survival time and poorer prognosis 21. In our study, we observed that expression of TCF1 (TCF7) was higher in NPC than non-cancerous nasopharyngeal mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…TCF1 (TCF7) has also been shown to be overexpressed in renal cell carcinoma 19. Interestingly, Shen et al demonstrated that another member of LEF/TCF family, TCF3, had a higher expression in NPC than in non-tumorous nasopharyngeal tissues, and they also confirmed that increased expression of TCF3 was closely related to clinical stage, locoregional recurrence and distant metastasis of NPC, and thus resulted in shorter survival time and poorer prognosis 21. In our study, we observed that expression of TCF1 (TCF7) was higher in NPC than non-cancerous nasopharyngeal mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been shown to have oncogenic activities in vitro in a variety of malignancies including prostate, 23,24 esophageal 25 and breast cancer, 26 glioblastoma, 27 and chronic lymphocytic leukemia 28 . Increased expression of TCF3 is associated with adverse outcome in a number of cancers 29–32 . Examination of Oncomine databases revealed increased expression of TCF3 in prostate cancer compared to benign prostate ( p < .01) in 9 of 16 databases (including all of the databases with increased MEX3D; examples in Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant activation of TCF3 (E2A), most commonly, was correlated with the risk and onset of lymphoblastic leukemia [ 37 ]. Associations between TCF3 and other human malignancies, such nasopharyngeal carcinoma [ 13 ], breast cancer [ 38 ], colorectal cancer [ 39 ], blastemal Wilms tumors [ 40 ], have been identified as well. In this study, the integrated bioinformatic analyses via Oncomine, GSE datasets, and TCGA-CESC database indicated that TCF3 was upregulated in multiple cancers, including CC, and its high expression was predicted to be correlated with poor outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…TCF3 protein exerts its cell type- or tissue-specific functions by forming a homodimer or a heterodimer with other bHLH proteins [ 9 ]. TCF3 was at first suggested to exert crucial functions during lymphocyte development [ 10 ], and studies have reported its involvement in the pathogenesis of several human malignancies, such as prostate cancer [ 11 ], breast cancer [ 12 ] and nasopharyngeal carcinoma [ 13 ]. Elevated expression of TCF3 has been associated with poor prognosis in CC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%